Vietnamese-English translation errors made by the fourth-year English majors: A case study at Bac Lieu University - Hoang, Quoc; Ta Thi, Kim Oanh (Technium Social Sciences Journal, 2025)
Having students to produce an error-free piece of translation has always been the life-long dream and the ambition of all Bac Lieu University teachers. The purpose of this study is to explore the translation errors made by the English majors in translating Vietnamese into English. To analyze the data, the researcher used both descriptive qualitative and quantitative research method and used error analysis procedure. The participants of this study consist of 4 English teachers and 46 English majors from the fourth-year in the academic year of 2024 - 2025. The main goal of this research is to find out common errors in Vietnamese-English translation made by students of Bac Lieu University, the teachers’ perception as well as students’ perception towards the causes of these translation errors. The results from the study indicates that the students make grammatical errors, lexical errors, and spelling errors. Based on the findings and discussion of the result, the researcher concludes that the students still face difficulties in using vocabulary and grammar.